2016
DOI: 10.1016/j.bjorl.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Association of tinnitus and hearing loss in otological disorders: a decade-long epidemiological study in a South Indian population

Abstract: The present study could identify the most prevalent otological risk factors leading to development of tinnitus with hearing loss in a South Indian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 19 publications
2
16
0
3
Order By: Relevance
“…Research in India reports that 4.5 million Indians had been diagnosed with tinnitus. 2 Epidemiological studies from the National Health and Nutrition Examination Survey (NHANES) in the United States report that up to 25.3% of the United States population has tinnitus and this data was confirmed by a study in Korea The National Health and Nutrition Examination Survey (KNHANES) reported that as many as 10,000 to 12,000 populations in South Korea are affected by tinnitus. Data from the United Kingdom national study of hearing states the prevalence of tinnitus patients wass 15.8% of the total UK population.…”
Section: Introductionmentioning
confidence: 89%
“…Research in India reports that 4.5 million Indians had been diagnosed with tinnitus. 2 Epidemiological studies from the National Health and Nutrition Examination Survey (NHANES) in the United States report that up to 25.3% of the United States population has tinnitus and this data was confirmed by a study in Korea The National Health and Nutrition Examination Survey (KNHANES) reported that as many as 10,000 to 12,000 populations in South Korea are affected by tinnitus. Data from the United Kingdom national study of hearing states the prevalence of tinnitus patients wass 15.8% of the total UK population.…”
Section: Introductionmentioning
confidence: 89%
“…Manche et al reported that almost 60.9% of CSOM cases are associated with tinnitus. 7 In this large epidemiological study involving a total of 3255 subjects, middle ear and inner ear diseases had a significant association with the development of tinnitus. Furthermore, almost all tinnitus subjects (96.9%) had hearing loss.…”
Section: Introductionmentioning
confidence: 93%
“…Although there have been advances in the specific literature of tinnitus, its pathophysiology and, consequently, its etiology have not been completely clarified. It is known that its etiology may be multifactorial, being associated with middle ear diseases, neurological, neurodegenerative, cardiovascular, metabolic and psychological disorders or, in the vast majority of cases, sensorineural hearing loss (3) . Although these are often concomitant symptoms, tinnitus is known to be perceived as more harmful by individuals than the negative implications of hearing loss (4) .…”
Section: Introductionmentioning
confidence: 99%